KEBIJAKAN LUAR NEGERI INDONESIA: (Kepemimpinan Habibie, Abdurrahman Wahid, Megawati dan Soesilo Bambang Yudhoyono) - Azmi, Agus Nilmada (Lintas Cendekia Publishing, 2023)
Foreign policymaking is always strongly related to international politics and domestic situations. These two aspects become determinant factors for the making of foreign policy in a country. Based on this research, it should be asked whether Indonesia’s foreign policy, Bebas Aktif (free and active). Reflecting on the emergence of the politic of Bebas Aktif that has been used as the guideline of Indonesian foreign policy, significantly during the cold war, and the changes in international system as well as national politics, this article will analyze the performance of Indonesian foreign policy after the fall of Soeharto’s regime.